EFFECT OF BAT GUANO ON SOME GROWTH ASPECTS OF WHEAT (Triticum aestivum L.) - & Al- mehemdi, Al- isawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Pot experiment was carried out at a greenhouse belongs to College of Education-University of Alanbar during winter season of 2013/2014 to investigate the effect of application of different levels of bat guano 0, 4 and 8 gm on some growth traits for two bread wheat triticum aestivum L. Cvs, one is local cv. (Aliz) another one is imported from Australia (Eratom). The experimental treatments were distributed under with factorial experiment arrangement 23 and 43.30 gm and root dry weight of 7.29 and 7.53, for each combination, respectively. It thus could be concluded that the application of bat guano at 8gm alone was the better than 4gm in some traits. However, the genetic affinity of local cv was dominated with 4gm application and of imported cv was to 8gm application. Some traits were measured as plant height, leaf area, leaf nos., tillers nos., root length, vegetative dry weight and root dry weight. Results revealed that bat guano application of 8gm was significantly superior in average of leaf nos of 33 leaves. Plant-1, tiller nos of (5.5 tillers. Plant-1) root length of 10.5 cm and vegetative dry weight of 40.27 gm. Local cv also significantly gave the highest average of leaf nos 29 leaves. Plant-1, root length 10.0 cm and vegetative dry weight 37.31 gm. Furthermore, the interaction combinations of 4gm with local cv and 8gm with imported one were superior in average leaf nos of 38 and 28 leaves. Plant-1, tiller nos of 7 and 5 tillers. Plant-1, root length of 11 and 10 cm, vegetative dry weight of 40.